Short term clinical outcomes for intravitreal dexamethasone implant in retinal vein occlusion patients [Retina ven tikanikligi olgularinda vitre içi deksametazon implantinin kisa dönem sonuçlar] - (:unkn) unknown (Gazi Eye Foundation, 2016)
Purpose: To evaluate short term results of intravitreal dexamethasone implant for macular edema due to retinal branch vein occlusion (BRVO) and central vein occlusion(CRVO). Material and Methods: 31 eyes of 31 patients (15 male,16 female, mean age:59.7) with either BRVO or CRVO were assessed during 6 months prospectively .Treatment naive patients who had <20/50 (Snellen Chart) of visual acuity with ≥250 μm of central macular edema (CME) were enrolled. During follow-up, all subjects received 0.7 mg intravitreal injection once.At each visit (preop.,1-3 and 6 months later) subjects were evaluated with best corrected visual acuity (BCVA,logMAR), central macular thickness (CMT, optical coherence tomography), slit-lamp examination and intraocular pressure. Lens opacities were assessed according to lens opacities classification III (LOCSIII) Results: BCVA (logMAR) improved with mean difference score of 0.12 (p<0.01) and 0.05 (p>0.05) at 3rd and 6th month visits, respectively in CRVO subjects. CMT (μm) decreased with mean difference of 177.75 μm (p<0.05) and 10.75μm (p>0.05) at 3rd and 6th month visits, respectively in CRVO subjects. BCVA (logMAR) improved with mean difference score of 0.17 (p<0.01) and 0.22 (p<0.05) at 3rd and 6th month visits, respectively in BRVO subjects.CMT (μm) decreased with mean difference value of 130 μm (p<0.05) and 51.75 μm (p>0.05) at 3rd and 6th month visits, respectively in BRVO subjects. 3 of 31 eyes which had high IOP (≥21 mmHg) were controlled with medical treatment. 8 of 31 cases had mild cataract and none need cataract surgery. Conclusions: Intravitreal dexamethasone implant can be considered as long term effective choice for CME with BRVO and CRVO compared to intravitreal anti-VEGF treatment. Moreover, it is a safer treatment alternative than triamcinolone for side effect of steroids. © 2016 Gazi Eye Foundation. All Rights Reserved.
Keywords: Cataract; Dexamethasone intravitreal implant; Intraocular pressure; Macular edema; Retinal vein occlusion